Gambaran Pelaksanaan Cuci Tangan 6 Langkah Pada Penunggu Pasien di Rawat Inap RSD Idaman BanjarbaruGambaran Pelaksanaan Cuci Tangan 6 Langkah Pada Penunggu Pasien di Rawat Inap RSD Idaman Banjarbaru - Devi Rahmayanti; Muhammad Hafz; Endang Pertiwiwati (School of Nursing, Faculty of Medicine and Health Science, Lambung Mangkurat University., 2023)
Background: A Hospital is a service that is required to be able to provide quality services to predetermined standards. One of the problems in service is nosocomial infection. In order to minimize its spread, standard precautions are applied, one of which is by washing hands using 6 correct steps which are a preventive program and hospital infection control in the national hospital accreditation standards. The importance of washing hands with the correct 6 steps is to reduce the risk of contracting the infection among patients, clinical staff, non-clinical, and visitors who are waiting patient at hospital.